2022
DOI: 10.1186/s12931-022-02105-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of matrix metalloprotease-2 and MMP-9 in experimental lung fibrosis in mice

Abstract: Background Idiopathic pulmonary fibrosis (IPF) is a diffuse parenchymal lung disease characterized by exuberant deposition of extracellular matrix (ECM) proteins in the lung interstitium, which contributes to substantial morbidity and mortality in IPF patients. Matrix metalloproteinases (MMPs) are a large family of zinc-dependent endopeptidases, many of which have been implicated in the regulation of ECM degradation in lung fibrosis. However, the roles of MMP-2 and -9 (also termed gelatinases A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 48 publications
1
16
0
1
Order By: Relevance
“…Acceleration of experimental diabetic nephropathy in MMP-2 knockout mice and prevention of cardiac ventricular fibrosis after myocardial infarction by MMP-2 secretion from mesenchymal cells also indicate the protective activity of MMP-2 in organ fibrosis [ 69 , 70 ]. The different models of lung fibrosis used in the experiment may explain the discrepant results previously reported by Bormann et al [ 42 ].…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Acceleration of experimental diabetic nephropathy in MMP-2 knockout mice and prevention of cardiac ventricular fibrosis after myocardial infarction by MMP-2 secretion from mesenchymal cells also indicate the protective activity of MMP-2 in organ fibrosis [ 69 , 70 ]. The different models of lung fibrosis used in the experiment may explain the discrepant results previously reported by Bormann et al [ 42 ].…”
Section: Discussionmentioning
confidence: 78%
“…Increased expression of hMMP-2 has been reported in pulmonary fibrosis, but whether it plays a pro-, antifibrotic, or no role remains unclear [ 58 , 59 ]. Bormann et al found no difference in the severity of pulmonary fibrosis between WT and MMP-2 knockout mice that orotracheally received an adenoviral vector carrying the cDNA of active porcine TGFβ1 [ 42 ]. However, other studies have shown that MMP-2 may degrade epithelial cell basement membrane, leading to inflammatory exudation, angiogenesis, and fibro-proliferative responses, and that MMP-2 may promote epithelial–mesenchymal transition by inducing aberrant activation of the Wnt/β-catenin signaling pathway [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Idiopathic pulmonary fibrosis (IPF) is a rare pulmonary disease of unknown cause, characterized by inflammation, and the progressive deposition of extracellular matrix that is associated with the formation of scar tissue leading to significant remodeling of the lungs [ 8 , 9 , 10 ]. IPF is a diffuse parenchymal lung disease (DPLD) [ 11 ] and it distinguishes itself from other DLPDs with a unique histological pattern known as usual interstitial pneumonia (UIP) [ 12 ]. UIP presents with significant lung volume loss, peripheral septal thickening, bronchiectasis, and a honeycomb pattern of fibrosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%